HEXACO Model and the Dark Triad: Findings on a Sample of the Employed, Women and Men - Gojković, Vesna; Dostanić, Jelena (Zbornik Instituta za kriminološka i sociološka istraživanja, 2017)
Numerous empirical studies have demonstrated that the underpinnings of socially aberrant behaviors constitute a distinctive personality domain. One line of research defines malignant personality through the Dark Triad – an assortment of conceptually independent yet empirically overlapping traits: narcissism, Machiavellianism and subclinical psychopathy. On the other hand, the negative pole of the basic personality factor Honesty-Humility defines maladaptive behaviors within the realm of the HEXACO model. The primary objective of this study was to investigate whether the relationship between the HEXACO model and the Dark Triad traits that has been established in the studies predominantly involving the young is equally applicable to the employed, adult population. Our secondary objective was to investigate sex-related differences with respect to socially aversive traits, as defined by both HEXACO and the Dark Triad approach. For this purpose, 234 women and 115 men (mean age 40.45 years) were administered SD3 and HEXACO – 60 psychometric scales. All participants were clinically healthy, without a criminal record and working in Serbia at that time. Quite in line with the existing literature, our data indicate that the HEXACO personality model and the Dark Triad share more than 50% of variance, with the negative pole of the Honesty-Humility factor accounting for approximately 25% of the common variance. Narcissism, of all Dark Triad traits, had the strongest association with the negative pole of Honesty-Humility. However, when Narcissism is separated from psychopathic/Machiavellian configuration it –together with the prosocial traits of the HEXACO model- contributes to socially desirable personality component. The men are best described by the Dark Triad traits, particularly by psychopathy, while women are characterized by Emotionality. We conclude that sex-related differences should be addressed in the context of HEXACO/Dark Triad relationship and that narcissism’s contribution to socially aversive behaviors deserves further investigation.